Association Between Temporal Changes in Diet Quality and Concurrent Changes in Dietary Intake, Body Mass Index, and Physical Activity Among Japanese Adults: A Longitudinal Study - Watanabe, Daiki; Murakami, Haruka; Gando, Yuko; Kawakami, Ryoko; Tanisawa, Kumpei; Ohno, Harumi; Konishi, Kana; Sasaki, Azusa; Morishita, Akie; Miyatake, Nobuyuki; Miyachi, Motohiko (Frontiers in Nutrition, 2022)
Background: Many cross-sectional studies have identified modifiable factors such as dietary intake, physique, and physical activity associated with diet quality but were unable to determine how a specific individual’s diet quality changes with these factors. These relationships may vary depending on an individual’s dietary intake. We aimed to determine the association between temporal changes in diet quality and concurrent changes in dietary intake, body mass index (BMI), and physical activity according to the diet quality trajectory pattern. Methods: This longitudinal prospective study included 697 Japanese adults aged 26–85 years, at baseline, with available data from at least two dietary intake surveys (4118 measurements). Dietary intake and physical activity were evaluated using validated dietary questionnaires and a triaxial accelerometer. Diet quality was calculated using the Nutrient-Rich Food Index 9.3 (NRF9.3), while physical activity was calculated based on the duration of activity performed at each level of intensity (sedentary, light, moderate, and vigorous). BMI was calculated from the measured height and weight. Statistical analyses involved latent class growth models (LCGM) and random-effect panel data analysis. Results: During a mean follow-up period of 6.8 years, NRF9.3 scores were assessed, on average, 5.4 times in men and 6.1 times in women. Based on the NRF9.3 score, three separate trajectory groups—‘low-increasing’, ‘medium-increasing’, and ‘high-stable’—among individuals aged 26–90 years were identified using LCGM. In the multivariate analysis, the NRF9.3 score trajectory was positively associated with energy intake, dietary fiber, vitamins A and C, magnesium, and food items, such as fruits and vegetables, and was negatively associated with BMI and the intake of saturated fats, sodium, and food items, such as meat, sugar, and confectioneries, even after adjusting for covariates. These relationships displayed heterogeneity across the identified NRF9.3 score trajectory groups. In the low-increasing group, an inverse relationship was observed between sedentary behaviour and NRF9.3 score trajectory. Conclusions: We identified modifiable factors associated with temporal changes in diet quality across a wide age range; however, these factors may vary according to the diet quality trajectories. Our findings may help develop effective strategies for improving diet quality, according to the trajectory of diet quality.